Determination of the number of superhelical turns by the hyperchromicity of partially denatured covalently-closed DNA molecules. - Dougherty, G (1982)
A novel method of determining the number of superhelical turns of a covalently-closed plasmid DNA is described. It relies on the determination of the hyperchromicity, and hence the proportion of unstacked basepairs, of a partially heat-denatured sample which co-migrates during electrophoresis with nicked circular duplex DNA. The values obtained for plasmid pBR beta G DNA at 4 degrees C (-29.8 and -33.5 in the two buffers used) agree closely with the values obtained in parallel by topoisomer band-counting. Our method is less precise than band-counting but is readily applicable to determining the superhelicity of very large DNA molecules. Our results confirm earlier findings that magnesium-containing buffers cause an increase in the duplex winding angle, and hence an increase in the number of negative superhelical turns.